Player migration and talent development in elite sports teams: A comparative analysis of inbound and outbound career trajectories in Danish and Norwegian women`s handball - Agergaard, S.; Ronglan, L. T. (Scandinavian Sport Studies Forum, 2015)
The conditions for national sport systems and talent development efforts are changing with the globalisation of sports. In the present study we explored the relationship between domestic talent development and the immigration of players from abroad through a comparative multiple-case study of Danish and Norwegian women`s handball. Quantitative data demonstrated how there has been a remarkable increase in not only the number, but also the performance level of immigrant players arriving into Danish women`s handball, in particular, in the first decade of the 2000s. Qualitative interviews were conducted with 12 experienced coaches and sport directors who have in-depth knowledge of group dynamics in elite handball. Using Lave and Wenger`s theory of situated learning in communities of practice the analysis demonstrated the ambiguous consequences of considerable immigration on the position and learning situation of domestic talent. Inbound trajectories of domestic talent may be supported by apprenticeship from many skilled role models (e.g. immigrant players), while an outbound trajectory may also appear, specifically if the young domestic players are continually hampered from participation in matches. It seems that it is not the high number of players from abroad, per se, that may block the development of local young talent, but first and foremost the structuring of training and match practices in the clubs and national leagues.